Synthesis of 2-iminothiazolidin-4-ones using guanine functionalized SBA-16 as a solid base catalyst. (23rd November 2021) - Gupta, Radha; Pathak, Devendra Deo
Graphical abstract: Graphical representation of 2-iminothiazolidin-4-ones synthesis using metal-free heterogeneous catalyst SBA-16@G. Abstract: The first example of a one-pot three-component tandem annulation approach is described for the synthesis of 2-iminothiazolidin-4-ones by the reaction of aromatic/aliphatic amines, aryl isothiocyanates, and ethyl bromoacetate, catalysed by guanine-functionalized SBA-16, [SBA-16@G], as an efficient and recyclable heterogeneous solid base catalyst. The methodology is simple and offers a broad-substrate scope under mild reaction conditions.